#TITLE_ALTERNATIVE# - TIMOTIUS SIMANGUNSONG (NIM : 13605055); Pembimbing 1 : Dr. Ir. Edy Suwondo; Pembimbing 2 : Ro, JUMADI
Data Reduction Program (DRP) is a software for calculating the performance, the interturbine gas temperature (T45H) trim value, and the efficiency of aircraft engine. DRP has been revised for several times. PT. Nusantara Turbin dan Propulsi (PT. NTP) has some documents containing Ã‚Â±20 years old DRP formula. PT. NTP currently uses the latest version of DRP at the test cell without the detail of the calculation process. Therefore, a validation is required for the engine performance calculation formula, the T45H trim formula, and the re-formulation of the engine efficiency calculation formula. This research uses data sample from five CT7-9C turboprop engines. DRP. The research is a comparison of calculation results of performance and T45H trim formulas owned by PT. NTP and the DRP calculation results. An error analysis also conducted to evaluate the validity of formula owned by PT. NTP. The research also includes a reformulation of efficiency formulas, its application, and a comparison with the DRP calculation results to evaluate its validity. The research shows CT7-9C engine performance and T45H trim formulas are valid by using criteria of maximum absolute error less than 2,5% at 95% confidence level. In the research, the CT7-9C engine efficiency formula have been re-formulated and validated. The T45H trim formulas also have been revised in order to comply the validation criteria.